The effects of heat-moisture modified tapioca starch on dough rheology and bread quality - Çetin Babaoğlu, Hümeyra (Afyon Kocatepe Üniversitesi)
In this study, the effects of substituting wheat flour with 5% and 10% tapioca starch (TS) or heat-moisture modified tapioca starch (MTS) on dough rheology and bread quality were investigated. The addition of MTS increased the water absorption of wheat flour (p<0.05). While the use of TS and MTS reduced stability, it increased the degree of softening (p<0.05). The highest stability (13.50 min) and the lowest degree of softening (22.00 BU) were found in the control sample (p<0.05). While the addition of TS did not change the maximum resistance value of the flour (p>0.05), the addition of 10% MTS decreased this value (p<0.05). The addition of MTS increased the moisture content of bread samples (p<0.05). No significant difference was determined among the specific volume values of the samples (p>0.05). With the addition of TS, L* and b* values in bread crusts increased, while the a* value decreased (p<0.05). The crust color values of bread samples containing 10% MTS were found to be similar to the control sample (p>0.05). With the addition of TS, the number of pores decreased and the area increased, resulting in fewer but larger pores (p<0.05), while the pore structure of bread samples produced with the addition of 5% MTS was found to be similar to the control sample (p>0.05). The substitution of MTS for wheat flour did not have a negative effect on the textural properties of bread samples (p>0.05). Specifically, 5% MTS can be substituted into wheat flour and used in bread production.

Bu çalışmada, buğday ununun %5 ve %10 oranında tapyoka nişastası (TS) veya ısı-nem uygulamasıyla modifiye edilmiş tapyoka nişastası (MTS) ile ikamesinin hamur reolojisi ve ekmek kalitesi üzerindeki etkileri incelenmiştir. MTS ilavesi, buğday ununun su absorbsiyonunu artırmıştır (p<0.05). TS ve MTS kullanımı stabiliteyi azaltırken, yumuşama derecesini artırmıştır (p<0.05). En yüksek stabilite (13.50 dakika) ve en düşük yumuşama derecesi (22.00 BU) kontrol örneğine ait bulunmuştur (p<0.05). TS ilavesi buğday ununun maksimum direnç değerini değiştirmemiştir (p>0.05), ancak %10 MTS ilavesi bu değeri azaltmıştır (p<0.05). MTS ilavesi ekmek örneklerinin nem içeriğini artırmıştır (p<0.05). Örneklerin spesifik hacim değerleri arasında önemli bir fark belirlenmemiştir (p>0.05). TS ilavesiyle ekmek kabuklarının L* ve b* değerleri artarken, a* değeri azalmıştır (p<0.05). %10 MTS içeren ekmek örneklerinin kabuk renk değerleri kontrol örneği ile benzer bulunmuştur (p>0.05). TS ilavesi ile gözenek sayısı azalırken toplam gözenek alanı artmıştır, dolayısıyla daha az ama daha büyük gözenekler oluşmuştur (p<0.05), %5 MTS ilavesiyle üretilen ekmek örneklerinin gözenek yapısı kontrol örneğiyle benzer bulunmuştur (p>0.05). Buğday ununa MTS ikamesinin ekmek örneklerinin tekstürel özellikleri üzerine olumsuz bir etkisi olmamıştır (p>0.05). Özellikle buğday ununa %5 MTS ikame edilerek ekmek üretiminde kullanılabilir.
Isı-nem uygulamasıyla modifiye edilmiş tapyoka nişastasının hamur reolojisi ve ekmek kalitesi üzerine etkileri
Keywords: Bread; Extensograph; Farinograph; Pore structure; Tapioca starch; Texture